Administración de productos financieros del Banco Nacional y su incidencia en la calidad del servicio a los clientes del cantón El empalme, periodo 2013-2014, propuesta de integración de cajeros automáticos. - Haro Chong, Alexandra Elizabeth (2015)
Ecuador Financial Institutions, banks and credit unions provided with financial products as the main source of financing using these entities, the National Development Bank with 87 years is the oldest bank in the service of Ecuador, since the government of Dr. Isidro Ayora on January 27, 1928, he created the Mortgage Bank of Ecuador, has a story to over 8 decades so that the March 28, 1974, the Official Gazette No. 526 of April 3 was published the same year, the new ORGANIC LAW National Development Bank is issued. With this Act, the National Development Bank takes economic, financial and technical autonomy. This research conducted the study of financial products offered by the National Development Bank branch in El Empalme periods 2013-2014 and their impact on the quality of services to its customers and the inhabitants of the canton, the problems described research theme as well as all financial services that the bank offers to its customers, the BNF gives priority attention to managing their balances, in granting the resources to invest in the development of mass production according to their activities and their coverage investment needs as a contribution to the Ecuadorian economy. In the canton El Empalme BNF 38 years of service to its customers has been offering products with security deposits, in granting loans, in policies, providing loans to bonds, use of ATMs, through the provision of services reliable, efficient and effective financial, to promote the economic development of families, productive sectors, communities and trading companies contributing to economic growth in the canton El Empalme, the province and the country.